123k views
5 votes
Solve for r in the formula S = L - rL.

2 Answers

2 votes
subtract L from both sides
S - L = L - L -rL
S - L = -rL
divide both sides by L
S - L/L = -rL/L
-r = S - L/L
divide both sides by -1
r = -S + L/L
User MattV
by
4.9k points
2 votes

Answer:

The value of the formula is
r=(L-S)/(L).

Explanation:

Consider the provided formula.


S = L - rL

We need to solve the provided formulafor r.

Subtract L from both side.


S-L=L-L- rL


S-L=-rL

Divide both sides by -L.


(S-L)/(-L)=(-rL)/(-L)


r=(-S+L)/(L)


r=(L-S)/(L)

Hence, the value of the formula is
r=(L-S)/(L).

User Psytho
by
5.5k points